Synthesis & characterization of nanostructure VO2 thin film - Ojha P.K.; Mishra S.K. (My University, 2025)
Vanadium dioxides are strongly correlated systems which undergo an insulator-metal transition (IMT) from a low-temperature semiconducting phase to a high-temperature metallic phase. Among them, Vanadium dioxide (VO2) undergoes IMT close to room temperature, accompanied by a structural transition resulting change of several orders of magnitude in the electrical and optical properties. Here, we present the synthesis of VO2 by sol-gel process which employs cost-effective precursors to synthesize pure phase of VO2 thin films. The synthesized thin films were characterized using an X-ray diffraction (XRD) to confirm phase purity and high resolution scanning electron microscope (HR-SEM) to study the crystallite and particle size for the synthesized films. The film's surface was analyzed by X-ray photoelectron spectroscopy (XPS) to determine the valence state and chemical composition of vanadium dioxide. © Content from this work may be used under the terms of the Creative Commons Attribution 3.0 licence.